Motivation as a key element of psychological potential for entrepreneurial activities among the retired military personnel - V. A. Komlev; E. A. Feoktistova (Вестник университета)
The article considers with the problem of diagnosing the motivation of military personnel leaving the reserve, in order to assess their psychological potential for entrepreneurial activity. The currently known approaches to assessing the psychological potential of entrepreneurial activity are analysed. The necessity of identifying diagnostics of motivation as a key element for predicting the success of a serviceman who is transferred to the reserve in creating his own business is noted. Based on the analysis of the research results obtained during the implementation of the national project “Small Business Course” for military personnel and members of their families, the most significant motivators for two types of entrepreneurs were identified: innovators (capable of generating new ideas and modifying them from a business plan) and imitators ( who prefer to distribute previously developed technologies).